Development of film-forming gel containing nanoparticles for transdermal drug delivery - Ngo, Hai V.; Tran, Phuong H.L.; Lee, Beom Jin; Tran, Thao T.D. (Nanotechnology, 2019)
Despite several studies on film-forming systems with the advantages of both the film and the hydrogel, there are still no effective systems for fast film formation with a high level of control over permeability. In this study, a film-forming system for the delivery of nanomedicine, termed a film-forming nanogel (FFN), was produced and investigated for the first time to meet this need. The objective of this research was to study a new generation of film-forming hydrogels (FFHs) loaded with curcumin nanoparticles (CUR-GNPs) for transdermal applications. FFHs were prepared by employing zein and HPMC 4000 as film-forming polymers. Meanwhile, CUR-GNPs were obtained by sonoprecipitation. The film-forming time, particle characteristics and FFN drug release profile were assessed. The optimized FFH had a smooth surface and a fast drying time of 6 min and 4.5 min in vitro and ex vivo, respectively. Additionally, high, sustained drug permeation from the FFN was observed after 24 h. The FFH containing CUR-GNPs showed potential for application in transdermal drug delivery with a fast film-forming time, uniform particle dispersion and high, sustained drug permeation.
Keywords: Effective systems; Film-forming; Gelatin nanoparticles; Nanogels; Particle characteristics; Particle dispersion; sonoprecipitation; Transdermal drug delivery; Administration, Cutaneous; Animals; Curcumin; Drug Carriers; Drug Delivery Systems; Drug Liberation; Hydrogels; Methylgalactosides; Nanoparticles; Particle Size; Permeability; Polymers; Skin; Skin Absorption; Solubility; Swine; film-forming hydrogel; gelatin nanoparticles; nanogel; sonoprecipitation; zein/HPMC